2005
DOI: 10.1037/0033-295x.112.1.75
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Context Model in Spatial Navigation and Relational Learning: Toward a Common Explanation of Medial Temporal Lobe Function Across Domains.

Abstract: The medial temporal lobe (MTL) has been studied extensively at all levels of analysis, yet its function remains unclear. Theory regarding the cognitive function of the MTL has centered along 3 themes. Different authors have emphasized the role of the MTL in episodic recall, spatial navigation, or relational memory. Starting with the temporal context model (M. W. Howard and M. J. , a distributed memory model that has been applied to benchmark data from episodic recall tasks, the authors propose that the entorhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

30
342
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 273 publications
(373 citation statements)
references
References 246 publications
(602 reference statements)
30
342
0
1
Order By: Relevance
“…More recently, we have seen an expansion of evidence challenging this dissociation [Jonides et al, 2008; Nee et al, 2008; Ranganath and Blumenfeld, 2005]. For example, it has been put forward that different local circuits mediate STM vs. LTM processes within the same cortical area [Gaffan, 2002; Howard et al, 2005]. By these views, the distinction between STM and LTM can be explained through differences in the intraregional neuronal dynamics within the same memory areas [Fuster, 2006, 2009], or through differences in the level of activity within these common memory areas/networks [Jonides et al, 2005; Postle, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have seen an expansion of evidence challenging this dissociation [Jonides et al, 2008; Nee et al, 2008; Ranganath and Blumenfeld, 2005]. For example, it has been put forward that different local circuits mediate STM vs. LTM processes within the same cortical area [Gaffan, 2002; Howard et al, 2005]. By these views, the distinction between STM and LTM can be explained through differences in the intraregional neuronal dynamics within the same memory areas [Fuster, 2006, 2009], or through differences in the level of activity within these common memory areas/networks [Jonides et al, 2005; Postle, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Episodic recall depends on an intact medial temporal lobe, a region of the brain that also supports a place code. Howard, Fotedar, Datey, and Hasselmo (2005) demonstrated that the leaky integrator that supports a gradually-changing representation of temporal context in TCM is sufficient to describe properties of cells observed in ventromedial entorhinal cortex during spatial navigation if it is provided with input about the animal's current velocity. This representation of temporal context generates noisy place cells in the open field, unlike the clearly-defined place cells observed in the hippocampus.…”
mentioning
confidence: 99%
“…1. The pattern of activity t i may be thought of as a pattern of sustained firing across cells in extrahippocampal MTL regions (Howard et al, 2005;Egorov, Hamam, Fransén, Hasselmo, & Alonso, 2002). The constraint that the length of t i is always equal to 1 means that t i lives on the surface of a hypersphere in a high-dimensional space.…”
mentioning
confidence: 99%
See 2 more Smart Citations